INTELLECTUAL CULTURE OF THE STAFF OF THE TRANSPORT INDUSTRY OF UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATION - SPITSINA, Anhelina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article substantiates the expediency of considering intellectual culture in the personnel management system of the transport industry of Ukraine in the conditions of European integration, its essence and structure are revealed. Emphasis is placed on the need to develop a culture of thinking, a culture of action and a culture of joint work as a kind of intellectual culture of the personnel of the transport industry. An innovative society is a highly intellectual community, which is characterized by intellectual knowledge, the desire to constantly improve the quality of intellectual activity and the realization of one's own ideas. Innovation as one of the elements of culture reflects the phenomenon of novelty in the process of modernization of the transport industry. The relationship between organizational, innovative and intellectual culture is determined. The instrumental and moral and ethical components of intellectual culture in the personnel management system are highlighted. The need for a comprehensive reform of the transport industry, its adaptation to the market conditions of business led to the need for reorganization and improvement of the personnel management system of transport enterprises. Study of intellectualization of activity enterprises became a natural result of the development of civilization and intellectual economy of the enterprise. New technologies are developed, new phenomena and facts are discovered, new theories and knowledge, new sciences appear. Their study is accompanied by the development of methodological research tools. Such intensive development of scientific potential affects the state of intellectual culture in society, resulting in the invention, rationalization, and mastering of fundamentally new technologies for the search, distribution, and translation of knowledge in the socio-economic space in order to ensure the competitive advantages of enterprises in the conditions of a market economy.Innovative activity necessarily requires a high level of intellectual culture, which will create a unique opportunity not only to obtain, but also to meaningfully reproduce a new quality of activity in the experience of other specialists
Keywords: intellectual culture; personnel management; transport industry; European integration; development conditions; innovative development